Genetic polymorphisms influence shear bond resistance of orthodontic brackets - Randazzo, Adam C.; Burnheimer, John M.; Bayram, Merve; Seymen, Figen; Vieira, Alexandre Rezende (Elsevier, 2020)
Objectives: The purpose of this study was to determine if shear bond resistance of orthodontic brackets bonded to enamel is associated with genes implicated in the enamel mineralization process.Methods: Ninety-two permanent, caries-free premolars extracted for orthodontic purposes and their associated saliva samples were obtained. Eighteen single nucleotide polymorphisms (SNPs) were studied for association with shear bond resistance. The genes of interest in this study were those previously associated with dental caries by our group. All tooth samples were bonded on the buccal surface with metallic lower lateral brackets, and then subjected to physical debonding. The force required to debond the bracket was recorded in Newtons (N) and converted to a shear bond resistance value in Megapascals (N/mm(2)). The data were analyzed for statistical significance as compared with the mean shear bond resistance value via PLINK whole genome analysis software.Results: Associations were found between the SNPs for tuftelin (rs7526319, P = 0.004) and amelogenin (rs17878486, P = 0.04) and a higher shear bond resistance.Conclusion: The collected data support the proposed hypothesis that genes involved in the mineralization process affect the bonding of orthodontic brackets, and such an association is of value for the field of orthodontics, particularly in evaluating the efficacy of enamel-resin bond strength for patients receiving treatment.
Keywords: Debonding; Enamel Surface; Genetics; Orthodontics; Shear Bond Resistance